REVITALISASI PASAR TERAPUNG LOK BINTAN DI BANJARMASIN DENGAN PENDEKATAN ARSITEKTUR KONTEKSTUAL - Al Faatihah; Wiwik Setyaningsih; Tri Yuni Iswati (ARSITEKTURA, 2014)
Abstract: Banjarmasin, Kalimantan Selatan designated as Heritage City in Indonesia by the United Nations Educational , Scientific , and Cultural Organization ( UNESCO ) , due to the history of Banjarmasin showed that it has famous rivers cultural values as citizens orientation activities. The one example of that cultural values is the floating market . Now , there has been a change in the socio- economic conditions of the community resulting in a reduced number of transactions , the total area and number of vendors , one of which occurred at the Floating Market Lok Baintan . This is what triggered the need for revitalization that is able to function as an effort to preserve the floating market in Banjarmasin cultural waters . The desain problem of that revitalization’s process is how to plan and design the supporting facilities that could integrated for keeping the cultural values and that can be a Banjarmasin city’s history laboratory. Beacuse of that , the strategy of “infill design” revitalization is very acceptable at the Floating Market Lok Bainta.Though contextual architecture’s concept, such as in designing elemnt and ornament that implent Banjarmasin’s identity that can be a facade and identity of region so that the this planning and designing process can be a one harmonious unit.  Keywords: Contextual Architecture, Floating Market, Maritim Cultural, Revitalization